The Enterprise Capital Structure Management Model - Bahatska, Kateryna; Batrakova, Tetiana; Silakova, Hanna; Klymash, Nataliia; Vialets, Oksana (My University, 2021)
Both empirical and theoretical methods of cognition are used to conduct the research. Methods of scientific observation and comparison are used to form the topic of scientific work, goals and objectives of the study. Methods of analysis and synthesis, induction and deduction, abstraction are used to determine the essential features of capital structure management. Methods of system structuring and modeling are used to create a mathematical model. The analogy method is used to find the weight factor of the objective function. The axiomatic method and the method of convergence from the abstract to the concrete were used for the practical application of the mathematical model, in particular, to analyze the dynamic index of related companies, stratified by size, industry, and so on.
Keywords: capital; model; management; structure; industrial enterprise; optimization; капітал; промислове підприємство; структура; управління; оптимізація; модель; кафедра фінансів